UNION OF SOVIET SOCIALIST REPUBLICS OF KAZAKHSTAN DURING WORLD WAR II UNDER STALIN’S RULE - Kara, Füsun (Bilecik Şeyh Edebali Üniversitesi, 2024)
Before World War II, Kazakhstan served Moscow with its fertile lands, rich human and mineral resources. Until World War II, the elimination of the economic and cultural inequality of the peoples had not yet been realized as planned. Like other Turkestan Turks, Kazakh Turks were against Soviet oppression. As a member of the Soviet Union, Kazakhstan played an active role in World War II, both on the front and behind the front. The only important event for the Communist Party was to win the victory. It was emphasized that the loss of human life was not important, what was important was the victory. Stalin established special construction companies from the indigenous peoples of Kazakhstan and Central Asia and the exiled workers. One in every four people of Kazakhstan's population was sent to the fronts and the war industry. Kazakh women fought on an equal basis with men, 5,183 Kazakh women received all military training and served in the most dangerous parts of the war, aircraft, tank and machine gun companies. The production of copper and lead from the Kazakh region, which is very rich in terms of mineral deposits, was important during the war, and Kazakhstan became one of the weapons depots of the Soviet Union from the first day of the war. In this study; general information about the geography of Kazakhstan and the Kazakh Turks was given, and the fact that the Kazakh lands were completely included in the Union of Soviet Socialist Republics after the Bolshevik Revolution, the general situation in the Kazakh Soviet Socialist Republic before World War II, the effects of World War II on the Kazakh Turks, the role of the Kazakh Turks in the Soviet Union winning the war, and the economy, science and art during this period were analyzed.

2. Dünya Savaşı öncesinde Kazakistan verimli toprakları, zengin insan ve maden kaynakları ile Moskova’ya hizmet etmiştir. 2. Dünya Savaşı’na kadar planlandığı gibi halkların ekonomik ve kültürel açıdan eşitsizliğinin ortadan kaldırılması henüz gerçekleşmemişti. Diğer Türkistan Türkleri gibi Kazak Türkleri de Sovyet baskısına karşı idiler. Kazakistan, Sovyetler Birliği’nin bir üyesi olarak 2. Dünya savaşında cephede ve cephe gerisinde aktif rol aldı. Komünist Parti için tek önemli hadise zaferin kazanılması idi. İnsan kaybının önem taşımadığı önemli olanın zafer olduğu vurgulandı. Stalin, Kazakistan ile Orta Asya’nın yerli halklarından ve sürgün edilenlerden işçi birliklerinden özel inşaat bölükleri kurdu. Cephelere ve savaş sanayisine Kazakistan nüfusunun her dört kişiden biri gönderildi. Kazak kadınları da erkekler ile eşit ölçüde savaştı. 5183 Kazak kadına askeri eğitim vermek sureti ile savaşın en tehlikeli olan bölümlerinden sayılan; uçak, tank ve makineli tüfek bölüklerinde görev verildi. Maden yatakları bakımından oldukça zengin olan Kazakistan bölgesinden bakır ve kurşun üretimi, savaş süresince önem arz etmiş, Kazakistan savaşın ilk gününden itibaren Sovyetler Birliği’nin silah depolarından birine dönüşmüştür. Bu çalışmada; Kazakistan coğrafyası ve Kazak Türkleri hakkında genel bilgi verilerek, Bolşevik İhtilali sonrasında Kazak topraklarının tamamen Sovyet Sosyalist Cumhuriyetler Birliği’nin terkibi altına girmesi, 2. Dünya Savaşı öncesinde Kazakistan Sovyet Sosyalist Cumhuriyeti’nde genel durum, 2. Dünya Savaşı’nın Kazak Türkleri üzerindeki etkileri, Sovyetler Birliği’nin savaşı kazanmasında Kazak Türklerinin rolü, bu dönemde ekonomi, ilim ve sanat analiz edildi.
II. Dünya Savaşı Döneminde Stalin'in Yönetiminde Kazakistan Sovyet Sosyalist Cumhuriyetler Birliği
Keywords: Turkish Society and Community; Türk Halkları ve Toplulukları